Navigating educational challenges: the resilience-boosting power of ai in students' interest - Deni Friska Yulianti,; Siska Saputri, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Artificial Intelligence (AI) powered tools and platforms have the potential to offer personalised learning experiences, catering to individual needs and providing innovative solutions to students' challenges. The study explored the transformative potential of AI in increasing students' engagement, interest, and resilience. The method used in this paper was a literature study employing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analysis) model, which was a systematic and transparent method for identifying, selecting, and synthesising relevant literature in research. The total number of articles reviewed was five articles from 30 articles from various sources. Implementing these AI-based methods has the potential to enhance students' engagement and resilience throughout their learning journey. However, it was crucial to acknowledge that the effectiveness of these approaches might have varied depending on the specific educational context and individual students' needs. This research significantly contributed to the knowledge related to AI's potential to fulfil teachers' limitations in designing creative, innovative classrooms. It is a roadmap to further investigate AI's potential applications in educational settings, aiming to address issues in the field of education, particularly in teaching and learning.